THE CATALYTIC ACTIVITY OF HETEROBIMETALLIC COMPLEXES CU/M (M=ZN, MN) SUPPORTED ON ACTIVATED CARBON IN THE REACTION OF HYDROGEN PEROXIDE DECOMPOSITION: UDC 541.49:542.97+661.183 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The catalytically active systems based on stone activated carbon and heterobimetallic complexes [Cu(L1/L2)][MCl4] (M = Zn, Mn; L1 – 4,6,6-trimethyl-1,9-diamino-3,7-diaza nona-3-ene; L2 – 1,15-dihydroxy-7,9,9-trimethyl-3,6,10,13-tetraza pentadeca-6-en) were obtained. It was shown that the support of the complexes on carbon surface stabilized their catalytically active state and increased the reaction yield of hydrogen peroxide decomposition.
Keywords: -